The Relationship between Coach Leadership, Training Motivation, and Training Discipline with the Character of Central Java Degree Fighting Athletes - Shinta Della Bestari; mugiyo hartono; Hermawan Pamot Raharjo (Journal of Physical Education and Sports, 2026)
Tarung Derajat is a martial sport native to Indonesia that has a peculiarity in the athlete character development system that is integrated with the training and competition process. The coaching is not only directed at achieving achievements, but also at instilling the values of discipline, responsibility, respect for coaches and organizations, and mental toughness. This study aims to analyze the relationship between coach leadership, training motivation, and training discipline on the character of Central Java Tarung Derajat athletes. The study used a quantitative approach with a correlational survey design. The research subjects amounted to 141 athletes who were declared to meet the analysis criteria from the total participants of the 2025 Provincial Sports Week (BK Porprov) Qualifying Round. Data collection was carried out using a questionnaire that measured the variables of coach leadership, motivation to train, training discipline, and athlete character. Data analysis uses the Spearman correlation test to look at partial relationships and multiple linear regressions to test simultaneous relationships. The results showed that coach leadership, training motivation, and training discipline had a positive and significant relationship with athlete character (p < 0.05). Simultaneously, the three variables showed a strong relationship with the athlete's character with a double correlation coefficient value of R = 0.681 and a contribution of 45.2%, with motivation to train as the most dominant variable. These findings confirm that the character of Tarung Derajat athletes is formed through the integration of effective coach leadership, strong motivation to practice, and the application of consistent and educational training disciplines.